Malignant rhabdoid tumor of the omentum in an adult male: a case report and literature review - Zhou, Xunjian; Duan, Zhi; Tao, Ting; Li, Zhen; Wang, Ning; Xu, Qimei; Wei, Meiyan; Zhong, Zheng; Liu, Ran; Yin, Qinghua; Xiong, Lixin; Chen, Hui (Frontiers in Oncology, 2023)
Malignant rhabdoid tumors (MRTs) are rare tumors with high mortality rates and poor prognoses. MRTs occur mainly in the central nervous system, kidneys, and soft tissues, but rarely in the omentum. MRTs occur more commonly in infants and children and less frequently in adults. Here, we report the first observed case of MRT in an adult omentum. A 35-year-old man with abdominal distension and pain was admitted to the emergency department. Previously, several hospitals considered patients with cirrhosis who had not received active treatment. Computed tomography and magnetic resonance imaging revealed diffuse omental thickening and massive ascites. The surgery was performed at our hospital, and the pathological diagnosis was MRT with a SMARCB1(INI-1) deletion. Postoperatively, his symptoms improved, and he underwent five cycles of chemotherapy. However, 6 months after surgery, the tumor developed liver metastases, and the patient subsequently died. Primary MRT of the greater omentum is rare, and its pathological diagnosis usually requires extensive clinicopathological evaluation of various differential diagnoses and an appropriate work-up to exclude other malignancies associated with SMARCB1 deletion. At the same time, the lack of specific signs of omental MRT and its rapid progression should alert clinicians.